Admission, outcome and referral pattern of admitted neonates: a cross-sectional descriptive study at selected district hospital SNCUs in Odisha - Sahu, Smitamayee; Subbarayalu, Yayathee (International Journal of Research in Medical Sciences, 2024)
Background: The state of Odisha is one of the leading states in the country for infant mortality in India. Odisha has established 44 special neonatal care units (SNCUs) to improve neonatal survival. The study aims to assess the morbidity, mortality, and referral trends to develop targeted suggestions to lower newborn deaths. Methods: We conducted a cross-sectional descriptive retrospective study on all admitted neonates, taking the secondary data from 8 SNCUs of District Hospitals in the State of Odisha for the period of 3 calendar years (2020-2022). We profiled the type of admission, age, gender, birth weight, admission indication, maturity, mortality profile and referral. Data was extracted in Excel 2021 and analyzed using Excel and Epi info. Results: Of the 43050 neonates admitted to the SNCU, 21069 (49%) were inborn. There were 58% male neonates. (59%, n=29401) were low birth weight neonates (<2500 gms); out of that, 869 babies (2%) were below 1000 gm. The median duration of stay in the SNCUs was 4 days. Perinatal asphyxia (n=13093) constitutes 30% of the admissions, followed by neonatal jaundice (7561, 18%), low birth weight <1800 gm (5728, 13%), refusal to feed (4745, 11%), and prematurity (n=3888, 9%). 75% of the total were discharged, 11% were referred, 10% died, and 4% left the SNCU against medical advice. The primary reasons for mortality & referral were birth asphyxia, hypoxic ischaemic encephalopathy (HIE), sepsis, and prematurity. Conclusion: Birth asphyxia is the primary cause of morbidity, mortality, and referral in newborns. Early referrals, effective intervention, and high-quality prenatal care are essential to prevent it.